Analisis Ancaman People Smuggling terhadap Keamanan Nasional Indonesia dalam Kasus Pengungsi Rohingya di Sumatera Utara - Rico Franc Janwar Sibero; I Gusti N. B. Sucitra; Yenti Garnasih (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The presence of refugees in Indonesia, particularly in North Sumatra, stems from smuggling activities orchestrated by transnational crime networks, which negatively impact the strategic intelligence components of Indonesia. This study focuses on analyzing the threat of people smuggling to Indonesia's national security in the case of Rohingya refugees in North Sumatra. The research employs a qualitative method by conducting interviews with several informants. The findings indicate that the primary threats include social conflicts, the expansion of transnational crime networks, and exploitation by vested interests, all of which constitute threats to national security and sovereignty. Meanwhile, the forms of threats posed by the smuggling of Rohingya refugees in North Sumatra to Indonesia's national security include ideological threats, political threats, economic threats, socio-cultural threats, and threats to national defense and security. Based on Robert Ring's threat classification, these threats are categorized as moderate. The intelligence strategy to address the threat of people smuggling involving Rohingya refugees focuses on maintaining national security stability. The means include upholding well-implemented policies and continuing cross-sector synergy and collaboration with international organizations to curb the activities of international smuggling networks. The approach involves enhancing public literacy and policy transparency as well as continuous monitoring of vulnerable smuggling areas.